2002
DOI: 10.1002/jbm.10070
|View full text |Cite
|
Sign up to set email alerts
|

In vitro behavior of albumin‐loaded carbonate hydroxyapatite gel

Abstract: Hydroxyapatite (HA) powder, porous HA, plasma-sprayed HA, apatite cements, and sintered HA have all been investigated as delivery systems for compounds such as human growth hormone and vancomycin. However, many previous studies showed that the period of release was limited to 2-3 weeks. The concept of using a nanoporous matrix as a means of immobilizing proteins is well known but has largely been confined to silica-based systems. Carbonate hydroxyapatite (CHA) is more soluble in vivo than HA, and when formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Whether this is a surface charge alteration affecting protein adsorption, cell attachment and differentiation, or a direct interaction between cell metabolism and bioavailable free Si is unclear. Protein conformation is sensitive to surface chemistry [47]; when calcium phosphates and specific proteins are combined under the correct conditions, calcium phosphate dissolution [48,49], nucleation [50] or ageing [51] can be modulated as can adsorbed protein species [49], conformation [52] and stability [53] demonstrating a reciprocal relationship between protein adsorption and calcium phosphate chemistry. More specifically, the quality and quantity of proteins adsorbed in vitro is sensitive to silicate substitution levels, which has a downstream effect on osteoblast-like cell attachment and metabolism [29].…”
Section: Biological Sensitivity To Silicate Substitution and Substitumentioning
confidence: 99%
“…Whether this is a surface charge alteration affecting protein adsorption, cell attachment and differentiation, or a direct interaction between cell metabolism and bioavailable free Si is unclear. Protein conformation is sensitive to surface chemistry [47]; when calcium phosphates and specific proteins are combined under the correct conditions, calcium phosphate dissolution [48,49], nucleation [50] or ageing [51] can be modulated as can adsorbed protein species [49], conformation [52] and stability [53] demonstrating a reciprocal relationship between protein adsorption and calcium phosphate chemistry. More specifically, the quality and quantity of proteins adsorbed in vitro is sensitive to silicate substitution levels, which has a downstream effect on osteoblast-like cell attachment and metabolism [29].…”
Section: Biological Sensitivity To Silicate Substitution and Substitumentioning
confidence: 99%
“…This local alignment of these ions are necessary for new bone formation. 25,26) This result suggests that the possibility to use the obtained microsphere as a scaffold of artificial implant due to an excellent biodegradability.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggested that the proteins were not derived from the urine itself, but were produced mostly as a result of the metabolism of dirt and grime by bacteria and mold. As is well known, proteins adsorb on the surface of apatite [23,24] and often inhibit the growth of apatite [25,26]. The formation of amorphous apatite in the scale might be partly attributed to the adsorption of the protein.…”
Section: Discussionmentioning
confidence: 99%